Design and Frame Strength Evaluation of Salt Washing Unit Capacity 50 Kg/hour - Tika Hafzara Siregar; Setya Permana Sutisna; Edi Sutoyo; Mamat Rahmat; Hablinur Al Kindi; Dodih (Master Program in Mechanical Engineering, Gunadarma University, 2023)
The salt washing unit is part of the salt processing machine. This unit's function is to wash raw salt with brine. This unit has a motor, agitator blade, washing chamber, and frame. The frame structure strength of the salt washing unit needs to be evaluated to ensure safety. This research aims to design the salt washing unit and obtain simulation results of frame structure strength to ensure the safety of the salt washing unit. This research was carried out by simulation to look for stress, strain, and changes in the shape of objects (displacement). The frame strength simulation was carried out using Solidwork software. The salt washing unit with a 50 kg/hour capacity has been designed. It has a cylindrical shape with 990 mm in height and 680 mm in diameter. From the simulation results of strain, it can be concluded that the minimum point is 1.80 × 108 Mpa, and the maximum point is 1.63 × 105 Mpa. From the simulation results of displacement, it can be concluded that the minimum point is 0 mm and the maximum point is 2,296 mm. The maximum stress is 5.254×106 N/m2, and the minimum stress point is 1.803×106 N/m2.